Complex Role of Capsaicin-Sensitive Afferents in the Collagen Antibody-Induced Autoimmune Arthritis of the Mouse. Issue 1 (December 2018) - Borbély, Éva; Kiss, Tamás; Szabadfi, Krisztina; Pintér, Erika; Szolcsányi, János; Helyes, Zsuzsanna; Botz, Bálint
Abstract Capsaicin-sensitive afferents have complex regulatory functions in the joints orchestrated via neuropeptides. This study aimed to determine their role in the collagen-antibody induced rheumatoid arthritis model. Capsaicin-sensitive nerves were defunctionalized by the capsaicin receptor agonist resiniferatoxin in C57Bl/6 mice. Arthritis was induced by the ArithroMab antibody cocktail and adjuvant. Arthritis was monitored by measuring body weight, joint edema by plethysmometry, arthritis severity by clinical scoring, mechanonociceptive threshold by plantar esthesiometry, thermonociceptive threshold by hot plate, cold tolerance by paw withdrawal latency from 0 °C water. Grasping ability was determined by the wire-grid grip test. Bone structure was evaluated byin vivo micro-CT and histology. Arthritic animals developed a modest joint edema, mechanical and cold hyperalgesia, weight loss, and a diminished grasping function, while thermal hyperalgesia is absent in the model. Desensitised mice displayed reduced arthritis severity, edema, and mechanical hyperalgesia, however, cold hyperalgesia was significantly greater in this group. Arthritic controls displayed a transient decrease of bone volume and an increased porosity, while bone density and trabecularity increased in desensitised mice. The activation of capsaicin-sensitive afferents increases joint inflammation and mechanical hyperalgesia, but decreases cold allodynia. It also affects inflammatory bone structural changes by promoting bone resorption.